The Diversity of Board of Directors Characteristics and Firm Value - Jonathan Steven John; Ricky Raharja Sudiono; Luciana Haryono; Yang Elvi Adelina (Journal of Applied Accounting and Taxation, 2020)
The research contributes to provide insights on how characteristics of board of directors can affect firm value by analyzing board characteristics such as gender diversity, age and educational background to firm value of public firms in Indonesia. Generational diversity is being considered as an independent variable as it has never been assessed in Indonesia. Resource dependence theory and upper echelons theory are used in this research among other available concepts to explain the impact of board characteristics during the decision-making process and its access to resources. ROA is used in this research as the profitability approach indicator of firm value, while Tobin’s Q is used as the market approach indicator of firm value. Samples used in this research amounts to 1.151 samples from 411 companies. The results show that educational background and board age significantly affects firm value positively when measured by profitability approach indicator. While gender diversity and generational diversity both have no significant effect on firm value when measured by either profitability approach indicator or market approach indicator due to homogeneity. The results indicate that the appointment of directors with older age while possessing higher education can increase a company’s firm value which is measured by profitability indicators.